Kesiapsiagaan Keluarga Pasien Yang Keluarganya Menderita Stroke Dalam Menghadapi Situasi Bencana Di Kota Ternate - Nur Santi Anwar; Nunung Iriani M.N. Doa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: The World Health Organization (WHO, 2016) states that there are several groups that are vulnerable when a disaster occurs, including children, pregnant women, the elderly, people with malnutrition and people with chronic diseases or immune disorders. Stroke as one of the groups affected by the disaster conditions that occurred. Stroke is a medical condition characterized by changes or neurological deficits caused by impaired blood supply to the brain, can be due to acute injury of the central nervous system (CNS) by vascular causes, including cerebral infarction, intracerebral hemorrhage and subarachnoid hemorrhage. in. Methods: This type of research is analytical descriptive with a cross sectional study approach. Result : There is still a lack of understanding of families, especially regarding aspects of actions that must be taken to anticipate disasters, not following the formulation of policies, emergency plans, disaster early warning systems, so that they do not support community preparedness.